Experimental Investigation of Radiation Emitted by Optically Thin to Optically Thick Wildland Flames. (7th April 2011) - Boulet, P.; Parent, G.; Acem, Z.; Kaiss, A.; Billaud, Y.; Porterie, B.; Pizzo, Y.; Picard, C.
Abstract : A series of outdoor experiments were conducted in a fire tunnel to measure the emission of infrared radiation from wildland flames, using a FTIR spectrometer combined with a multispectral camera. Flames of different sizes were produced by the combustion of vegetation sets close to wildland fuel beds, using wood shavings and kermes oak shrubs as fuels. The nongray radiation of the gas-soot mixture was clearly observed from the infrared emitted intensities. It was found that the flame resulting from the combustion of the 0.50 m long fuel bed, with a near-zero soot emission, may be considered as optically thin and that the increase in bed length, from 1 to 4 m, led to an increase in flame thickness, and therefore, in flame emission with contributions from both soot and gases. A further analysis of the emission was conducted in order to evaluate effective flame properties (i.e., emissivity, extinction coefficient, and temperature). The observation of emission spectra suggests thermal nonequilibrium between soot particles and gas species that can be attributed to the presence of relatively cold soot and hot gases within the flame.